PENGEMBAGAN LKPD TERINTEGRASI HOTS TERHADAP KETERAMPILAN PROSES IPAS SISWA KELAS V SDN 104211 MARINDAL I - Nur Husnul Fadliah; Safrida Napitupulu, Rita Destini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research focuses on the development of HOTS-integrated student worksheets (LKPD) for IPAS process skills. The adjectives of the research are to produce a HOTS-integrated LKPD, analyze its feasibility, and assessment student responses to the HOTS-integrated LKPD. The research employs the ADDIE development model, which consists of five stages: Analysis Design, Development, Implementation and Evaluation.The research involves validating the material, the LKPD itself, and administering questionnaires for teacher and student responses. The subjects of the research are fifth-grade students at SDN 104211 Marindal 1, including 15 students (6 males and 9 females). The results of the HOTS-integrated LKPD development show that the LKPD has a media validation score of 80%, which is categorized as "feasible"; LKPD validation is also at 80%, categorized as "feasible"; the teacher response questionnaire score is 90%, categorized as "feasible"; and the student response questionnaire score is 88,1%, indicating that students are "very interested" in the HOTS-integrated LKPD. Thus, the HOTS-integrated LKPD is deemed suitable for use in enhancing IPAS process skills.